Sexually Transmitted Infections in A Tertiary Hospital of Kathmandu: A Retrospective Study - Paudel, Sushil; Parajuli, Niraj; Dahal, Sudip; Paudel, Sudarshan (Nepal Journal of Dermatology, Venereology & Leprology, 2021)
Introduction: Sexually transmitted infections (STIs) are the diseases that are transmitted by sexual contact if a partner is infected with agent known to cause infection of genitalia. This group of diseases pose a huge public health problem. This study aims to provide an insight on the prevalence of STIs in a tertiary care center dedicated to civil servants. Methods: This is a retrospective cross-sectional study. All patients diagnosed with STI in a dermatology out-patient of Civil Service Hospital, a tertiary care hospital situated in Kathmandu over a period of two years from January 1 2018 to December 30 2019 were included in the study. The diagnosis was made by clinical and laboratory investigations. Results: The total number 157 cases of STIs were enrolled in this study, of which 119 (75.8%) were males and 38(24.2%) were females. The mean age of patients was 27.8±8.8 years, ranging from 15 to 60 years. Seventy three (46.5%) patients were married, while 81 (51.6%) patients were unmarried. Unmarried males were significantly more vulnerable to acquire STIs (p=0.005). Males were having significantly more premarital or extramarital sexual exposures as compared to females (p<0.001). The most common presentation was condyloma acuminata in 84(53.5%) patients. Consistent use of condom was reported only in 3 (2.5%) males and 1 (2.6%) females in this study. No association was noted between the education level attained to the practice of safe sexual methods (p=0.535). Conclusion: The proportion of males was higher than females in our study which might be due to the reluctances of female to see doctor for sexual problems. The level of education did not seem to make people aware of practicing safe sex. Sexual education seems must in all level of education.